A reduction in long-term spatial memory persists after discontinuation of peripubertal GnRH agonist treatment in sheep. (March 2017) - Hough, D.; Bellingham, M.; Haraldsen, I.R.; McLaughlin, M.; Robinson, J.E.; Solbakk, A.K.; Evans, N.P.
Highlights: Peripubertal GnRHa impaired long-term spatial memory. This impairment was not reversed after discontinuing GnRHa-treatment. Spatial orientation and learning performance remained unaffected following GnRHa withdrawal. Speed of progression through these spatial tasks was altered after discontinuing GnRHa. GnRH irreversibly alters these cognitive functions during critical window of development. Abstract: Chronic gonadotropin-releasing hormone agonist (GnRHa) administration is used where suppression of hypothalamic-pituitary-gonadal axis activity is beneficial, such as steroid-dependent cancers, early onset gender dysphoria, central precocious puberty and as a reversible contraceptive in veterinary medicine. GnRH receptors, however, are expressed outside the reproductive axis, e.g. brain areas such as the hippocampus which is crucial for learning and memory processes. Previous work, using an ovine model, has demonstrated that long-term spatial memory is reduced in adult rams (45 weeks of age), following peripubertal blockade of GnRH signaling (GnRHa: goserelin acetate), and this was independent of the associated loss of gonadal steroid signaling. The current study investigated whether this effect is reversed after discontinuation of GnRHa-treatment. The results demonstrate that peripubertal GnRHa-treatment suppressed reproductive function in rams, which was restored after cessation of GnRHa-treatment at 44 weeks of age, as indicated by similar testes size (relative to body weight) in both GnRHa-Recovery and Control rams at 81 weeks of age. Rams in which GnRHa-treatment was discontinued (GnRHa-Recovery) had comparable spatial maze traverse times to Controls, during spatial orientation and learning assessments at 85 and 99 weeks of age. Former GnRHa-treatment altered how quickly the rams progressed beyond a specific point in the spatial maze at 83 and 99 weeks of age, and the direction of this effect depended on gonadal steroid exposure, i.e. GnRHa-Recovery rams progressed quicker during breeding season and slower during non-breeding season, compared to Controls. The long-term spatial memory performance of GnRHa-Recovery rams remained reduced ( P  < 0.05, 1.5-fold slower) after discontinuation of GnRHa, compared to Controls. This result suggests that the time at which puberty normally occurs may represent a critical period of hippocampal plasticity. Perturbing normal hippocampal formation in this peripubertal period may also have long lasting effects on other brain areas and aspects of cognitive function.